The mediation of the memories of the Marquesa de Santos in his old manor house in São Paulo (Cadernos de Sociomuseologia, 2021)
The article presents the Solar da Marquesa de Santos, currently the headquarters of the Museum of the City of São Paulo, which, among other uses, was the residence of Domitila de Castro Canto e Melo in the mid-19th century. The Marquesa de Santos is one of the rare female characters in the consecrated history of the country, whose figure has circulated through various media over time. Considering the forms of appropriation of the house and the stories of its famous owner, it seeks to discuss the challenges imposed by the relationship between the expectations of the public and the reality of its exhibition spaces, understanding the role of heritage education as a way of mediating gender issues aroused during visitation.Keywords: Heritage Education; Gender; Solar da Marquesa de Santos.